ISLAM IDEOLOGI KAUM TERTINDAS: COUNTER HEGEMONY KAUM MARGINAL DAN MUSTAD’AFÎN - Thahir, Lukman S. (Hunafa: Jurnal Studia Islamika, 2009)
Islam is perceived as being not only a new religion by some writers of history, but also as a liberating force. The teaching of Islam—the main source of which is the Qur’an—contains a lot of teaching on liberation the oppressed from the oppressors. The Qur’an even firmly expresses  that the Prophet Moses was sent to liberate the oppressed from despotic ruler (Pharaoh). In this context,  Islam appears as an  ideology that can be employed to liberate the oppressed from the despotic power. Kata Kunci: Islam, ideologi, kaum tertindas, kaum marginal